2015
DOI: 10.1039/c5ra03354c
|View full text |Cite
|
Sign up to set email alerts
|

Diketo acids and their amino acid/dipeptidic analogues as promising scaffolds for the development of bacterial methionine aminopeptidase inhibitors

Abstract: Using diketoesters as the template, various derivatives were designed and the selected compounds were synthesized as bacterial methionine aminopeptidase (MetAP) inhibitors. The results of in vitro antibacterial screening revealed fifteen compounds (1a-c, 1e-h, 1j, 1l, 2a-c, 3d, 5c and 5e) as potent against different bacterial strains. By using the MTT assay on human cell line (HepG2), the viability of cell proliferation was evaluated and nine compounds (1c, 1e, 1j, 1l, 2a,b, 3d, 5c and 5e) showed no cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In extension of our work on the synthesis of bioactive small molecule inhibitors, we adopted a simple and efficient synthetic pathway to achieve the title compounds as shown in Scheme . The key intermediate, indole‐chalcone 1 was prepared by condensation of commercially available indole‐3‐aldehyde and 3‐nitroacetophenone in the presence of piperidine.…”
Section: Resultsmentioning
confidence: 99%
“…In extension of our work on the synthesis of bioactive small molecule inhibitors, we adopted a simple and efficient synthetic pathway to achieve the title compounds as shown in Scheme . The key intermediate, indole‐chalcone 1 was prepared by condensation of commercially available indole‐3‐aldehyde and 3‐nitroacetophenone in the presence of piperidine.…”
Section: Resultsmentioning
confidence: 99%
“…31.25 mg mL À1 for C. albicans. At predetermined time periods (0, 2,4,6,8,10,12,14,16,18,20,22, and 24 h) aer incubation with agitation at 37 C, 1 mL aliquot to each sample was removed from the conical ask and growth was measured turbidometrically at 600 nm using Thermo Multiskan spectrophotometer. Optical density (O.D.)…”
Section: Biologymentioning
confidence: 99%
“…In our continuous efforts to design biologically active heterocycles, [12][13][14][15][16][17] we hypothesized albaconazole as a model for preparation of 1,2,3-triazole derivatives of quinazolin-4(3H)-one (5a-q and 6a-q) and studied their antifungal properties. Further, single crystal X-ray study of compounds 2 and 5c has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Human erythrocytes from healthy individuals were collected in tubes containing EDTA as anti-coagulant. The erythrocytes were harvested by centrifugation for 10 min at 2000 rpm, 20 C and washed three times in PBS. To the pellet, PBS was added to yield a 10% (v/v) erythrocytes/PBS suspension.…”
Section: Hemolytic Assaymentioning
confidence: 99%
“…Therefore, it has lent additional urgency to develop new molecular scaffolds having novel mode of action or to modify existing drug molecules. Considering the large pharmacological importance of b-lactams and in extension to our efforts to explore novel biologically active molecules 19,20 , we synthesized novel N-benzyl-3,4-diaryl substituted 2-azitidinone (b-lactam) derivatives (4a-g, 4i-s), while compounds 4h and 4t were isolated as highly substituted 1,3-oxazin-4-one derivatives. In silico pharmacokinetic and toxicity parameters were also assessed for all the synthesized compounds.…”
Section: Introductionmentioning
confidence: 99%